2003
DOI: 10.1128/jvi.77.14.7830-7842.2003
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chimeric Feline Foamy Virus-Based Retroviral Vectors for the Induction of Antiviral Immunity in Cats

Abstract: In order to define the potential and applicability of replication-competent foamy virus-based vaccine vectors, recombinant feline foamy virus (FFV) vectors encoding defined segments of the feline calicivirus (FCV) capsid protein E domain were constructed. In cell cultures, these FFV-FCV vectors efficiently transduced and expressed a hybrid fusion protein consisting of the essential FFV Bet protein and the attached FCV E domains. The stability of the vectors in vitro was inversely correlated to the size of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…For instance, we recently showed that replication-competent vectors that are directly related to the replicationdeficient ubi-lacZ vectors are efficient at expressing a heterologous vaccine antigen without any side effects. 6 In order to use the current vectors in animal experiments, we employed the constitutively active human ubi C promoter for transgene expression as this promoter displays long-term activity in several cell types from men and a broad range of animals. 37 In addition, mapping of vector integration sites in the authentic animal model will become possible considering the success of the cat genome sequencing project.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, we recently showed that replication-competent vectors that are directly related to the replicationdeficient ubi-lacZ vectors are efficient at expressing a heterologous vaccine antigen without any side effects. 6 In order to use the current vectors in animal experiments, we employed the constitutively active human ubi C promoter for transgene expression as this promoter displays long-term activity in several cell types from men and a broad range of animals. 37 In addition, mapping of vector integration sites in the authentic animal model will become possible considering the success of the cat genome sequencing project.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Additionally, replication-competent FFV-based vaccine vectors induce a partially protective immunity against a highly pathogenic challenge virus in cats. 6 In one of our previous studies, we have demonstrated that FFV self-inactivating (SIN) vectors rapidly give rise to replication-competent revertants (RCRs) indicating that additional genetic deletions are required to generate safe vectors. 4 In a following study, we determined that the essential cis-acting sequences required for FFV-based vectors are located upstream and around the gag start codon and inside pol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated applicability, efficiency, and safety of replication-competent feline FV (FFV) vectors for the transfer of vaccine antigens into cats. 19 More important for medical application, replication-deficient FV-based vectors carrying substantial deletions in structural and regulatory genes have been shown to be especially suited for the long-term transduction of human haematopoietic stem cells. [20][21][22] However, the proposed transduction of haematopoietic stem cells or other long-lived cells demands that RCRs are not generated in the patient.…”
Section: Introductionmentioning
confidence: 99%
“…This deletion is compatible with vector replication in vitro and in cats. 19,27 Each of two independent clones of the novel SIN vectors pCF-SIN (#2 and #8) and pCF-Bet-Gfp-SIN (#6 and #8) was characterized in detail.…”
Section: Introductionmentioning
confidence: 99%